Clinical and electrocardiographic features of patients with myocardial infarction with non-obstructive coronary artery disease (MINOCA). Issue 2 (February 2021) - dal Fabbro, Jan; Candreva, Alessandro; Rossi, Valentina A.; Shahin, Mohammady; Yousif, Nooraldaem; Lüscher, Thomas F.; Duru, Firat; Denegri, Andrea
Abstract : Aims: Myocardial infarction with non-obstructive coronary artery disease (MINOCA) is often an underdiagnosed and undertreated condition. This study aimed to evaluate clinical and ECG characteristics of MINOCA in a large cohort of patients admitted for acute coronary syndrome. Methods: All coronary angiograms performed at the University Heart Center in Zurich (Switzerland) between 2012 and 2016 were investigated. MINOCA was defined according to European Society of Cardiology guidelines and patients were divided into two groups, based on the presence or absence of coronary sclerosis at angiogram[nonobstructive coronary artery disease (noCAD) and normal coronary arteries (NCA)]), after exclusion of myocarditis and Takotsubo syndrome. Results: Out of 13 669 angiographic studies, 3695 were diagnosed with acute coronary syndrome; of these, 244 patients presented MINOCA (6.6%). Patients with noCAD were more likely to be older (67.9 vs. 59.2 years, P  < 0.001) with higher prevalence of traditional cardiovascular risk factors (hypertension 64.1 vs. 41.2%, P  = 0.002; diabetes 19.7 vs. 10.8%, P  = 0.036; hypercholesterolemia 36.6 vs. 23.5%, P  = 0.037). On surface ECG, anterior ST- segment elevation was more frequent in NCA patients (13.7 vs. 5.0%, P  = 0.016). Secondary prevention therapy was significantly more prescribed in noCAD compared with NCA patients (acetylsalicylic acid 68.3 vs. 21.6%, P less than 0.001; statins 76.1 vs. 22.5%, P less than 0.001; angiotensin-converting enzyme inhibitor–AT1 blockers 51.4 vs. 31.3%, P  = 0.006). One-year mortality was very low (0.4% for noCAD patients). Conclusion: noCAD patients were older, with higher prevalence of cardiovascular risk factors and more frequently discharged with secondary prevention therapy. NCA patients presented more frequently anterior ST- segment elevation. Further diagnostic tests should be highly recommended to determine the underlying mechanism of MINOCA.